Innovation in teacher professional development and collaborative practices - Vincent-Lancrin, Stéphan; Urgel, Joaquin; Kar, Soumyajit; Jacotin, Gwénaël (2019)
This chapter presents the change in teacher professional development practices. They typically take two forms: formal training (in content knowledge or pedagogy) and peer learning through collaborative practices (for example collaboration in the preparation of lessons). The change within countries is presented as an increase or decrease in the share of students exposed to the practice. The percentage point change is also expressed as a standardised effect size in the final table.